Interactions of polar lipids with cholesteryl ester multilayers elucidate tear film lipid layer structure - Paananen, Riku O; Viitaja, Tuomo; Olżyńska, Agnieszka; Ekholm, Filip S; Moilanen, Jukka; Cwiklik, Lukasz (The ocular surface, 2020)
PURPOSE: The tear film lipid layer (TFLL) covers the tear film, stabilizing it and providing a protective barrier against the environment. The TFLL is divided into polar and non-polar sublayers, but the interplay between lipid classes in these sublayers and the structure-function relationship of the TFLL remains poorly characterized. This study aims to provide insight into TFLL function by elucidating the interactions between polar and non-polar TFLL lipids at the molecular level. METHODS: Mixed films of polar O-acyl-ω-hydroxy fatty acids (OAHFA) or phospholipids and non-polar cholesteryl esters (CE) were used as a model of the TFLL. The organization of the films was studied by using a combination of Brewster angle and fluorescence microscopy in a Langmuir trough system. In addition, the evaporation resistance of the lipid films was evaluated. RESULTS: Phospholipids and OAHFAs induced the formation of a stable multilamellar CE film. The formation of this film was driven by the interdigitation of acyl chains between the monolayer of polar lipids and the CE multilayer lamellae. Surprisingly, the multilayer structure was destabilized by both low and high concentrations of polar lipids. In addition, the CE multilayer was no more effective in resisting the evaporation of water than a polar lipid monolayer. CONCLUSIONS: Formation of multilamellar films by major tear film lipids suggest that the TFLL may have a similar structure. Moreover, in contrast to the current understanding, polar TFLL lipids may not mainly act by stabilizing the non-polar TFLL sublayer, but through a direct evaporation resistant effect.
Keywords: lipidy; Lipids; mastné kyseliny; estery cholesterolu; slzy; Cholesterol Esters; Fatty Acids; Tears